The Implementation of The Total Physical Response (TPR) Technique to Develop Young Learners Vocabulary of Recognizing Colours - Wilda Hasanah; Muhammad Andriana Gaffar (Journal of Educational Sciences, 2026)
Introducing English from an early age is a crucial step toward foreign language acquisition. However, young learners often encounter challenges when learning a language that is unfamiliar to them. This study aims to examine the effectiveness of the Total Physical Response (TPR) method in improving English color vocabulary among early childhood learners. This study employed a qualitative approach using classroom action research conducted at Al Asthoriyah Early Childhood Education Center and Mekar Arum Kindergarten in Bandung Regency. Data were collected through classroom observations, field notes, and semi-structured interviews with teachers. The findings indicate that the implementation of the TPR method through engaging and movement-based activities enhanced students’ comprehension and responsiveness to instructions. Students demonstrated high levels of enthusiasm and motivation, which contributed to noticeable improvement in vocabulary acquisition and faster response in answering questions. Based on these findings, the TPR method can be considered an effective and engaging instructional approach that offers a practical solution to challenges in early English language learning.